Al-Qarinah (Circumstantial Evidence) and its capacity in criminal cases, Munakahat and wealth convictions according to Islam - Abdul Mutalib, Lukman; Wan Ismail, Wan Abdul Fattah; Baharuddin, Ahmad Syukran; Mohamed, Mohd Faisal; Abd Murad, Abdul Hamid; Mohd Wafa, Kamarul Arifin; Suhid, Asmawati (Science and Engineering Research Support Society, 2020)
The most crucial goal of the Islamic judicial system is to uphold justice. Reasonable judgment is a form of justice. Judgment signifies judging in a prudent, meticulous, accurate and appropriate manner as Allah Almighty has determined. According to the law, the claimant or prosecution must prove his or her claim. There are several types of proof methods. Among them is al-Qarinah. Al-Qarinah in language means sign. From a terminology perspective, it is a description of the situation that reached the level of confidence. Nonetheless, scholars differ in the extent to which al-qarinah is accepted in the law conviction, especially in the case of hudud and qisas. The Islamic evidence law is, in fact, dynamic and current. It is entirely independent of its reality and its environment. It demands change in keeping with the rapid development of science and technology. Today most of the evidence for criminal cases such as adultery, rape, theft and so on is not proven by syahadah, pledge or oath, but it is calling for al-Qarinah. Science and technology have changed human civilization and their attitudes. Crime is increasingly complex and challenging to prove. At the same time, the discovery of science is becoming more and more powerful. DNA evidence, fingerprints, blood tests, CCTVs and more have replaced the role of syahadah, pledge even when the evidence presented by al-Qarinah is sometimes more accurate and convincing. Therefore, this paper attempts to evaluate fuqaha practices of al-qarinah and to obtain a distinct illustration of its position as a method of proving in Islam. The research method used is the literature study which is to evaluate the past and current texts related to al-Qarinah using comparative and descriptive techniques. The findings of the research show that al-Qarinah was adopted as a law conviction from a trivial issue to a hudud problem.